2006
DOI: 10.1038/sj.pcan.4500858
|View full text |Cite
|
Sign up to set email alerts
|

Nephrostomies in obstructive uropathy; how should hormone resistant prostate cancer patients be managed and can we predict who will benefit?

Abstract: Current opinion advocates the use of nephrostomies in hormone naive patients with obstructive uropathy while hormone resistant patients require an individual approach. Patients undergoing a nephrostomy for uropathy were retrospectively analysed, with particular interest in hormone status and blood levels. Over a 46-month period, 26/112 nephrostomies were performed for prostate cancer induced uropathy. Survival was 226.5 days for hormone naive patients, 114.3 days in the responsive group and 100.2 days if resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
(14 reference statements)
0
23
0
Order By: Relevance
“…In contrast to obstructive uropathy causedbystones,thebiologicalgenesisinprostatecanceris extrinsic, caused by external compression of ureter or bladder,orindirectlybyelevationofthetrigone.Whileastentin patients suffering from urolithiasis simply facilitates passage of the concrements, it needs to resist external compression andinvasioninthecaseofmalignantcompression.Thus,even ifastentisabletobypasstheinternalureteralnarrowing,it willlikelyfailovertime [15].Thismightexplainlowersuccess ratesforstentingofextrinsicobstructionasopposedtointrinsicocclusion [16,17].Thedifferentsortsofreportedstentsdid not allow a systematic assessment of the impact of different stent materials on the outcome in prostate cancer patients. Atpresent,polyurethaneandsiliconearethemostfrequently usedmaterialsinclinicalpractice.Thereisawidevariability inoverallsurvivalofprostatecancerpatientswithobstructive uropathy,dependingondiseasecharacteristicsotherthanobstruction.Thelongestrecordedoverallsurvivalamountedto 26months [6].Thepresenteddatadonotallowacomparison ofoverallsurvivalforthethreeinterventionmodesPCN,retrogradestenting,andAD.Theresultssuggestinferioroverallsurvivalinpatientspre-treatedwithADorknownasAD resistantcomparedtohormone-naivepatients.Theseresults correspond with clinical experience in patients with other There are several problems concerning the validity and generalisabilityoftheseresultsbecausethepublishedstudies showanumberofprofoundmethodologicalflaws.Firstly,the numberofincludedpatientsperstudyissmall.Additionally, some studies report general results on various pelvic malignancieswithoutseparateanalysisofprostatecancerpatients. Asecondmajorissueconcerningthevalidityandcomparabilityofdataistheepidemiologicaldesignofthestudies.Most publisheddataarisefromcaseserieswithpotentiallyconsiderabledifferencesinpatientcharacteristics,whichmayhave a profound impact on differences in recorded outcomes and reduce the comparability of the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to obstructive uropathy causedbystones,thebiologicalgenesisinprostatecanceris extrinsic, caused by external compression of ureter or bladder,orindirectlybyelevationofthetrigone.Whileastentin patients suffering from urolithiasis simply facilitates passage of the concrements, it needs to resist external compression andinvasioninthecaseofmalignantcompression.Thus,even ifastentisabletobypasstheinternalureteralnarrowing,it willlikelyfailovertime [15].Thismightexplainlowersuccess ratesforstentingofextrinsicobstructionasopposedtointrinsicocclusion [16,17].Thedifferentsortsofreportedstentsdid not allow a systematic assessment of the impact of different stent materials on the outcome in prostate cancer patients. Atpresent,polyurethaneandsiliconearethemostfrequently usedmaterialsinclinicalpractice.Thereisawidevariability inoverallsurvivalofprostatecancerpatientswithobstructive uropathy,dependingondiseasecharacteristicsotherthanobstruction.Thelongestrecordedoverallsurvivalamountedto 26months [6].Thepresenteddatadonotallowacomparison ofoverallsurvivalforthethreeinterventionmodesPCN,retrogradestenting,andAD.Theresultssuggestinferioroverallsurvivalinpatientspre-treatedwithADorknownasAD resistantcomparedtohormone-naivepatients.Theseresults correspond with clinical experience in patients with other There are several problems concerning the validity and generalisabilityoftheseresultsbecausethepublishedstudies showanumberofprofoundmethodologicalflaws.Firstly,the numberofincludedpatientsperstudyissmall.Additionally, some studies report general results on various pelvic malignancieswithoutseparateanalysisofprostatecancerpatients. Asecondmajorissueconcerningthevalidityandcomparabilityofdataistheepidemiologicaldesignofthestudies.Most publisheddataarisefromcaseserieswithpotentiallyconsiderabledifferencesinpatientcharacteristics,whichmayhave a profound impact on differences in recorded outcomes and reduce the comparability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analyses donebysomeauthorsshoweddifferencesinoverallsurvival dependingoncertainpatientcharacteristics:Accordingtothe results of Bordinazzo et al [11] and Chiou et al [3], overall survivalisnotsignificantlydifferentinpatientswithunilateral andbilateralobstruction(20-21months).Harrisetal. [6]re-portedshorteroverallsurvival,withbilaterallyobstructedand mainly hormone-refractory patients having a much shorter survivaltimethanpatientswithunilateraluretericobstruction (5.3 vs. 2.4 months). The subgroup analyses of five publications [2,3,6,11,13]comparingpatientswithformerADtreatmentandAD-naivepatientsshowatrendforlongersurvival inAD-naivepatients.Thisfindingissupportedbythedataof Michigan and Catalona [14] who treated patients with AD onlyandshowedmarkedlyreducedoverallsurvivalinpatients notrespondingtothistreatment.3studiescomparedoverall survivalofpatientswhohaddecompressionwithpatientswith no performed decompression [1,2,13] in cohorts including bothAD-naiveandhormone-refractorypatients.WhileHonnens de Lichtenberg et al [1] and Paul et al [2] detected a shorteroverallsurvivalinpatientswhoweredecompressedas opposedtopatientswithoutPCNorstent,KhanandUtz [13] report a survival in the treatment arm that is slightly higher thanthatinthecontrolarmwithnodecompression.ThepresentedstudiesdonotallowcomparisonofoverallsurvivalbetweenPCNandretrogradestenting.Althoughthereareoverall survival data on patients receiving PCN, the only study evaluatingretrogradestentingdoesnotreportoverallsurvival [10].The3publicationsthatincludedpatientstreatedeither withPCNorretrogradestentingdidnotperformasubgroup analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically with regard to PCN tube insertion, two studies did not find a significant difference in overall survival when only unilateral relief of a bilaterally obstructed system was performed, 62,63 and one study found a difference in patients with hormone refractory status. 64 A more recent study by Nariculam and associates 65 suggests that the serum creatinine nadir after PCN tube insertion was roughly similar whether unilateral or bilateral tubes were inserted. On the basis of the limited evidence, it appears that if PCN tube placement is to be performed, the clinician need only divert the better functional unit.…”
Section: New Directions With Endoscopic Therapy For Upper Tract Obstrmentioning
confidence: 97%
“…While nephrostomy drainage is widely offered for hormone-naïve ureteral obstruction, controversy exists regarding the use of nephrostomy tubes for hormoneresistant ureteral obstruction, which is thought to portend a worse prognosis. Harris and Speakman [16] compared their experience with nephrostomy drainage for patients with hormone-naïve versus hormone-resistant disease. Twenty-six patients were retrospectively identified: two were hormone naïve, three were responding to hormones, and 21 were hormone resistant.…”
Section: Ureteral Obstructionmentioning
confidence: 99%